2015
DOI: 10.2989/1814232x.2015.1076519
|View full text |Cite
|
Sign up to set email alerts
|

Gastric lavage as a non-lethal method for stingray (Myliobatiformes) diet sampling

Abstract: Understanding the trophic interactions of ecologically important mesopredators such as Myliobatiformes(stingrays) is vital, but, given their susceptibility to overexploitation, the collection of stomach contents for dietary analysis necessitates the use of non-lethal methods. We provide a detailed method of using gastric lavage to collect stomach contents from the 'Vulnerable' porcupine ray Urogymnus asperrimus at the St Joseph Atoll of the Amirantes Group, Seychelles. Rays were captured by hand, inverted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Thus, 55 U . asperrimus were hand captured during daylight hours in May and June 2014 and subjected to non‐lethal gastric lavage for the collection of stomach contents (Elston et al , ). The fish were captured only on the reef flats because acoustic telemetry revealed that: U .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, 55 U . asperrimus were hand captured during daylight hours in May and June 2014 and subjected to non‐lethal gastric lavage for the collection of stomach contents (Elston et al , ). The fish were captured only on the reef flats because acoustic telemetry revealed that: U .…”
Section: Methodsmentioning
confidence: 99%
“…The capture and gastric lavage technique are detailed in Elston et al (), but briefly, U . asperrimus were approached from behind until close enough to lunge and place a gloved hand around the base of the tail.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ecologists typically use δ 13 C in animal tissues to determine the source of primary production in consumer diets (DeNiro and Epstein 1978;Tieszen et al 1983;Peterson 1999) and δ 15 N to assess the trophic level of consumers within a food web (DeNiro and Epstein 1981;Post 2002;Vanderklift and Ponsard 2003). The use of stable isotopes to trace consumer resource use is advantageous over traditional methods such as gut content analysis as stable isotope sampling can be less invasive (e.g., small tissue sample collected for stable isotopes vs. lethal sampling, O'Shea et al 2013 or gut flushing, Barnett et al 2010;Elston et al 2015 to collect stomach contents) and can shed light on resources used over longer time periods (Tieszen et al 1983;Hussey et al 2012a), as opposed to just the most recently used resources.…”
mentioning
confidence: 99%